Reassessment of Risk Genotypes (GRN, TMEM106B, and ABCC9 Variants) Associated With Hippocampal Sclerosis of Aging Pathology. Issue 1 (January 2015) - Nelson, Peter T.; Wang, Wang-Xia; Partch, Amanda B.; Monsell, Sarah E.; Valladares, Otto; Ellingson, Sally R.; Wilfred, Bernard R.; Naj, Adam C.; Wang, Li-San; Kukull, Walter A.; Fardo, David W.
Abstract : Abstract: Hippocampal sclerosis of aging (HS-Aging) is a common high-morbidity neurodegenerative condition in elderly persons. To understand the risk factors for HS-Aging, we analyzed data from the Alzheimer's Disease Genetics Consortium and correlated the data with clinical and pathologic information from the National Alzheimer's Coordinating Center database. Overall, 268 research volunteers with HS-Aging and 2, 957 controls were included; detailed neuropathologic data were available for all. The study focused on single-nucleotide polymorphisms previously associated with HS-Aging risk: rs5848 ( GRN ), rs1990622 ( TMEM106B ), and rs704180 ( ABCC9 ). Analyses of a subsample that was not previously evaluated (51 HS-Aging cases and 561 controls) replicated the associations of previously identified HS-Aging risk alleles. To test for evidence of gene-gene interactions and genotype-phenotype relationships, pooled data were analyzed. The risk for HS-Aging diagnosis associated with these genetic polymorphisms was not secondary to an association with either Alzheimer disease or dementia with Lewy body neuropathologic changes. The presence of multiple risk genotypes was associated with a trend for additive risk for HS-Aging pathology. We conclude that multiple genes play important roles in HS-Aging, which is a distinctive neurodegenerative disease of aging. Abstract : Supplemental digital content is available in the text.